Development of environmental movements in Kazakhstan through the prism of social and political transformations: key trends and current issues - B., Kuzembayeva A.; S., Baikushikova G.; F., Delovarova L.; S., Chukubayev Y. (Farabi Journal of Social Sciences, 2019)
Abstract. The purpose of this paper is to determine the political significance of the ecological movements in Kazakhstan through the analysis of NGO’s activity, contribution of authorities and civil initiatives on the national level. Ecological situation in Kazakhstan is very tense and complicated: the environmental problems at the local level cannot compete with other social problems, particularly, problems of socialeconomic nature, and as a result, they are not perceived adequately. The unresolved environmental issues are a distinct threat to Kazakhstan’s national security and challenging to the regional one in Central Asia. It is clearly visible tendency to ignore ecological imperatives and focus on the current fossil fuel based energy economy. In this regard, civil society initiatives on environmental protection are becoming notably topical. The paper deals with the tendencies of modern ecological movement in Kazakhstan as a kind of associated interest groups. The authors give a brief history of roots and development of this movement and analyze its distinguishing characteristics as a new participant of political life. A special attention is paid on the analysis of the measures on improving the ecological situation and prove the necessity in reforming this sector. The authors conclude the article with possible mechanisms of a larger involvement of citizens and increase the efficiency of NGO’s activity in the ecological sphere.